Systematic Literature Review (SLR): The Effect of Ice Breaking on Student Learning Outcomes - Risma Oktafia, Risma Oktafia; Elisa Septiana, Elisa Septiana; Ramdhani Alifatus Saidah; Wieline Dewi Azzahra, Wieline Dewi Azzahra; Fina Fakhriyah, Fina Fakhriyah; Erik Aditya Ismaya (Jurnal Prajaiswara, 2023)
Abstract— Ice breaking is an activity or technique that is carried out between lessons with the aim that students can receive material again in a relaxed and enthusiastic atmosphere. The problem that occurs in learning is that usually students easily get bored with the class atmosphere which is monotonous and tends to be conventional. This study aims to determine the effect of ice breaking on student learning outcomes. The method used in this study is the Systematic Literature Review (SLR) method. The use of the Systematic Literature Review (SLR) method aims to review all research related to the topic of the phenomenon to be studied. Data collection in this study began by searching for articles on the Google Scholar database through the Publish or Perish (PoP) application using the keyword "Ice breaking in elementary schools", with year limits starting from 2017 to 2023. The articles found at the start of the search were 200 articles, then included up to 10 articles that really fit the criteria of this study. Based on this research, it was found that the application of ice breaking techniques can improve student learning outcomes. This is evidenced by the results of a literature review of 10 articles that have been interpreted by researchers with the topic of the effect of applying ice breaking techniques on learning outcomes.